(untitled) (Journal of Oriental Studies, 2024)
The article introduces the problem of justification of the right to power of four righteous calipհs, as well as the analysis of the mechanisms of election and major factors that have influenced the election process. The issues that have appeared after death of Prophet Muhammad related to the election of the new leader, the authority and obligations of the latter and major principles of governance. In this regard it is worth mentioning that in case of each caliph the election mechanism was unique and had principal differences in each case and were influenced strongly by political and economic context of the given time period. The facts introduced in the article allow to conclude that there were two major factors that have influenced the election process: tribal and clan affiliations on one hand and religeous-ideological on another. Moreover correlation between these two change in favor of the tribal and clan affiliations, which is strongly influenced by the growth of political and economic power among certain circles of the Quraish tribe.